Universidade aberta à terceira idade (UNATI): desafios e possibilidades - Martins, Ana Luiza Prates [UNESP] (2015)
The present work to discuss the challenges and active aging possibilities. It presents the university extension program - UNATI engaged in the search for a worthy , participative and active aging.